2021
DOI: 10.1029/2021ja029262
|View full text |Cite
|
Sign up to set email alerts
|

PROBA2 LYRA Occultations: Thermospheric Temperature and Composition, Sensitivity to EUV Forcing, and Comparisons With Mars

Abstract: The Earth's thermosphere, the upper region of its neutral atmosphere, extends from the temperature minimum at the mesopause (85-100 km;Xu et al., 2007) to geospace. Spanning the regions of both the ionosphere and Low Earth Orbit, the thermosphere and its state have important implications for space weather (Schunk & Sojka, 1996). Photochemical and dynamical processes in the thermosphere change its temperature, density, and composition, directly influencing satellite drag and trans-ionospheric electromagnetic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 46 publications
3
5
0
Order By: Relevance
“…The noted m and r values of ∼2.63 ± 0.24 (∼1.70 ± 0.20) and ∼0.67 (∼0.56) at Earth (Mars), respectively, indicate that the terrestrial response to the solar rotation in flux is significantly stronger than that at Mars for a similar density level (Table 1 and Figure 4 contain more quantitative analyses). This result confirms previous findings (e.g., Bougher et al., 1999, 2015, 2017; Forbes et al., 2006, 2007; Keating & Bougher, 1987, 1992; Thiemann & Dominique, 2021), reporting reduced sensitivities to solar irradiance for Mars' thermosphere generally explained by the increased importance of CO 2 cooling in damping solar EUV energy at Mars. The lower correlation for Mars may be due to short‐term density variability not associated with solar effects.…”
Section: Correlation Analyses and Comparative Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…The noted m and r values of ∼2.63 ± 0.24 (∼1.70 ± 0.20) and ∼0.67 (∼0.56) at Earth (Mars), respectively, indicate that the terrestrial response to the solar rotation in flux is significantly stronger than that at Mars for a similar density level (Table 1 and Figure 4 contain more quantitative analyses). This result confirms previous findings (e.g., Bougher et al., 1999, 2015, 2017; Forbes et al., 2006, 2007; Keating & Bougher, 1987, 1992; Thiemann & Dominique, 2021), reporting reduced sensitivities to solar irradiance for Mars' thermosphere generally explained by the increased importance of CO 2 cooling in damping solar EUV energy at Mars. The lower correlation for Mars may be due to short‐term density variability not associated with solar effects.…”
Section: Correlation Analyses and Comparative Resultssupporting
confidence: 92%
“…Consistent with our understanding of the increased importance of CO 2 cooling in damping solar EUV energy at Mars, Earth's daytime thermospheric density sensitivity to flux is found to be ∼10%–50% larger than that of Mars for a similar density level. This result is in excellent agreement with earlier studies (e.g., Forbes et al., 2006) and the recent work by Thiemann and Dominique (2021) that showed Mars' exospheric EUV temperature sensitivities to be about 0.47 as sensitive to EUV variability as those at Earth. Similar to previous Martian (e.g., Hughes et al., 2022) and terrestrial (e.g., Thiemann, Dominique, et al., 2017) studies, Mars' thermospheric density response to EUV forcing is shown to increase with altitude up to ∼240 km (with m values up to ≃2.8%/%).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations